Prevalence of Asymptomatic Bacteriuria in School Aged Children: A Screening Study - Sarah Sabah Hasan Alshami; Nidhal Awad Obaid Alibraheemi; Mohanad Qasim Mahfoodh Abdullah (International Journal of Medical Sciences And Clinical Research, 2026)
Background: Asymptomatic bacteriuria (ASB) is a common but often missed condition in school-aged children affected children remain asymptomatic, persistent bacteriuria may predispose high-risk groups to recurrent urinary tract infections and renal complications and the data regarding the prevalence and associated factors of ASB among Iraqi school-aged children are limited. Aim of the study: To determine the prevalence of asymptomatic bacteriuria among school-aged children and to identify factors associated with its occurrence. Patients and methods: Prospective cross-sectional screening study was conducted at Karbala Health Directorate primary health care centers from July to December 2025 and included total of 194 school-aged children (6–14 years) attending the primary care. Children with urinary symptoms, recent antibiotic use, or known urinary tract abnormalities were excluded. Data were collected using a questionnaire that included clinical assessment, urinalysis, urine culture, and relevant laboratory investigations. Asymptomatic bacteriuria was defined as significant bacterial growth on urine culture in the absence of urinary symptoms. Results: The prevalence of asymptomatic bacteriuria was 6.7% (13/194). Escherichia coli was the most commonly isolated organism (62%), followed by Klebsiella, Proteus, and Enterococcus species. Pus cells, positive nitrite test, and bacteriuria on microscopy were significantly more common among children with ASB (p